When we were orphans - Ishiguro, Kazuo (Faber and faber, 2000)
In 1930s England, Christopher Banks has become one of the country's most celebrated detectives; his cases are the talk of London society. Yet one crime has always haunted him: the mysterious disappearance of his parents in Old Shanghai, when he was a boy.